Micro-learning Platforms Brand Awareness Using Socialmedia Marketing and Customer Brand Engagement - Mujica, Alejandro (2021)
This study aims to analyse the impact of Social Media Marketing in Customer Brand Engagement and Brand Awareness micro-learning platforms. The sample consisted of 220 students from micro-learning platforms using social media in the educational institutions. Because social-media marketing and customer brand- engagement are second-order reflexive constructions, the two-stage approach of hierarchical models with mode-A was adopted. The results reveal that social media marketing influences both the building of customer brand engagement and brand awareness among students on micro-learning platforms. Furthermore, it was shown that customer brand engagement is an important mediator between social media marketing and brand awareness. Social-media marketing activities carried out by micro-learning platforms contribute to the generation of customer brand-engagement and brand awareness of these institutions. Furthermore, the results show that, although social-media marketing helps to generate brand-awareness, it is through customer brand-engagement that social-media marketing is most effective in generating brand-awareness. For micro-learning platforms, the results allow them to understand the importance of customer brand-engagement when using social-media marketing to generate brand-awareness.